Research and realities politics in the Third World - Rebullida, Ma. Lourdes G. Genato (Third world perspectives on politics series, 2020)
"The Third world perspectives on politics series draws together scholarly articles from Kasarinlan: Philippine journal of third world studies ..."--Page preceding title page.